Influence of heat treatment on the conductivity of nickel-based superalloys - Nagarajan, Balasubramanian (2018)
Non-destructive measurement of residual stress at the subsurface of nickel-based alloys using eddy current method has been limited by its sensitivity to its microstructure, especially to the precipitates. This paper investigates the effect of heat treatment on the electrical conductivity of RR1000, a nickel-based superalloy with a large fraction of γ’ precipitates. Different heat treatment conditions, ranging from solution heat treatment to precipitation hardening with different aging times and temperatures, are used to achieve varying initial microstructures. Hardness of the samples is measured first to quantify the heat treated samples followed by the measurement of electrical conductivity using the conductivity probes of frequencies between 1 MHz and 5 MHz. The relationship between the hardness and conductivity of the heat treated samples is then correlated further. The results highlight the significant influence of heat treatment on the sample hardness and the electrical conductivity of RR1000.